The Effect of Leverage, Earnings Per Share on Stock Prices with Dividend Policy as a Moderating Variable (Study on Banking and Financial Services Companies Listed on the Indonesia Stock Exchange) - Sudibyo, Heru Harmadi (IJOSMAS, 2021)
Investors will conduct various analyzes to obtain information on whether the company is able to provide compensation for the investments they have invested. One of them is with fundamental analysis. This study aims to determine the effect of bag and leverage, Earning Per Share (EPS) on stock prices with Dividend policy as a Moderation variable. In this study, the ratio used to assess company performance is leverage, earnings per share (EPS), for dividend policy is the dividend payout ratio (DPR). The object of this research is the Banking and Financial Services Companies listed on the Indonesia Stock Exchange (IDX). The research method in this study is a qualitative research method with a quantitative approach. The population used was 58 companies, then the determination of the sample was determined through a purposive sampling technique. Based on the established criteria, a sample of 21 companies was obtained. The results showed that there was no significant partial effect of the Debt to Equity Ratio variable on stock prices. Partially, Earning Per Share is a variable that has a partial and significant effect on stock prices. There is a significant partial effect of the variable Divident payout ratio on stock prices. There is an interaction of Debt to equity ratio and Earning per share variables with this dividend payout ratio, identifying that investors need to calculate the size of the Earning Per Share value, because the size of the Earning Per Share affects changes in stock prices in the capital market. This shows that the company must maintain the value of the Earning Per Share variable.